Navigating the Intersection of Corporate Governance and Corporate Tax Planning: A Scoping Review - Nasir, Noor Emilina Mohd; Yaacob, Najihah Marha; Kamarudin, Siti Nurhazwani; Rashid, Norfadzilah; Othman, Nik Norlaili Jamilah Nik (Advances in Social Sciences Research Journal, 2024)
The scoping review analyses the convergence of corporate governance and corporate tax planning. The aim of this review is to identify the publication trends, key issues and areas of limited understanding in the current academic literature. Corporate governance structures balance the interests of shareholders, management and other stakeholders. Tax planning, on the other hand, involves strategies aimed at reducing an organisation's tax liability while ensuring compliance. Recent studies point to a intricate relationship between these two areas. The extent and form of tax planning activities can be influenced by corporate governance mechanisms, including ownership structure and board composition. Strong, independent boards may be more inclined to favour tax strategies that are consistent with long-term value creation rather than resorting to aggressive tax planning strategies. Hence, the objective of this review relevant academic articles, focusing on research that examines the relationship between corporate governance characteristics and corporate tax planning. This will provide a basis for future research that can further investigate this important relationship. Overall, this scoping review aims to provide a comprehensive overview of the current state of knowledge on the influence of corporate governance on companies' tax planning practises. This information can provide valuable insights to policymakers, regulators and business leaders in their efforts to create a fair and open tax environment.